Vitamin D status in children with leukemia, its predictors, and association with outcome. Issue 4 (11th January 2020) - Jackmann, Natalja; Mäkitie, Outi; Harila‐Saari, Arja; Gustafsson, Jan; Nezirevic Dernroth, Dzeneta; Frisk, Per
Abstract: Background: Children and adolescents with leukemia are potentially at high risk of vitamin D inadequacy, which may have clinical relevance for skeletal morbidity, infections, and cancer outcome. This study aimed to evaluate vitamin D status at the time of diagnosis to investigate its predictors and association with overall survival in children with leukemia. Procedure: We included all 295 children and adolescents diagnosed with leukemia at our institution between 1990 and 2016 who had available serum sample from the time of diagnosis. We analyzed serum 25‐hydroxyvitamin D and parathyroid hormone levels and correlated them with clinical data. Results: The 25‐hydroxyvitamin D level was deficient (< 25 nmol/L), insufficient (25‐50 nmol/L), sufficient (50‐75 nmol/L), and optimal (> 75 nmol/L) in 6.4%, 26.8%, 39.7%, and 27.1% of the children, respectively. Older age and a more recent time of sampling (calendar year) predicted lower 25‐hydroxyvitamin D level. In preschool children (age ≤6 years), lower 25‐hydroxyvitamin D level was also associated with acute myeloid leukemia, and a 25‐hydroxyvitamin D level < 50 nmol/L was associated with inferior overall survival. In school‐aged children (age > 6 years), the 25‐hydroxyvitamin D level showed significant seasonal variation. Conclusion: It remains unclear whether vitamin D supplementation in pediatric leukemia patients will improve outcome.